Belief Towards Organic Farming Among Farmers of Ranchi District - Singh, Nidhi; Rajan, Neha; Singh, Ajeet Kumar; Kumar, Anjani; Pandey, Brijesh; Singh, Ravindra Kumar (Indian Journal of Extension Education, 2019)
Organic farming aims to produce crops using natural inputs and to eliminate toxic substances from farming system to provide healthy and toxicity free food to consumers. Of late, Government of India has promoted the organic farming at a large scale. Organic farming is not a new concept but it is a traditional farming with modern technology. In line with this, three villages of Angara block of Ranchi District have been developed as organic villages. The study was conducted to assess the belief of farmers after implementation of organic inputs on the land and produced organic foods. For the study, two villages of the Ranchi district Budhakocha and Dhurleta were selected. Questionnaire on General, Attitudinal, Practical and Normative Belief of Organic Farming (Hindi) was used along with interview for data collection. Sample size of the study was 30 (15 of each village). The findings of the study showed that 100 per cent farmers believed that organic farming is good while 60 per cent of the population practically belief that organic farming is beneficial of them. 53 per cent of the population agreed with limitations which hindered in persuading organic farming.
Keywords: Attitudinal belief; Control belief; General belief; Organic farming